Systems Approach to Efficient Field Machinery Utilization for Lowland Rice Production - Bockari-Gevao, Sakr Marvin (2005)
Within the agricultural sector, there are wide variations in the level and pattern of energy use among various crops. To assess this energy demand, quantitative data on operating conditions is required for each unit operation. With the current increase in world population, energy consumption needs effective planning. One way to optimize energy consumption in agriculture is to determine the efficiency of methods and techniques used. This study was carried out with the ultimate aim of developing a model that could be used for estimating the energy consumption in a lowland rice production system and to predict the potential yield of rice from operational energy inputs and from quality indices of tillage and planting operations. Tillage systems obtained with factorial combinations of tractor forward speeds obtained from four transmission gear selections and three rotary tilling speeds were compared with respect to effective field capacity and energy requirements for implements used in the typical sequence for each system. The effects of the rotary tillage systems on irrigated soil properties in terms of changes in bulk density, cone index, plasticity index, aggregate uniformity coefficient and organic matter content were also investigated. Energy analysis for the entire production process included the operational energy consumption by field machinery and human labour, and the indirect energy accounted for by fertilizer, pesticides and seeds used, Functional relationships that allow the quantification of the different processes in the developed simulation model were formulated essentially through the use of secondary data and through curves fitting to some real data. Mathematical equations from agricultural machinery management and empirical equations were employed. Results from the tillage experiment indicate that differences in field capacity, and fuel and total energy requirements for each tillage system can be attributed primarily to many factors such as soil moisture, soil density, rotary tilling speed, and operation speed and depth. Average total energy inputs in the lowland rice production system (excluding irrigation energy) summed up to about 12225.97 ha-I. As main consumers of energy, fertilizer (7721 .O3 ha-'; 63.2%) and fuel use (2717.82 MJha- '; 22.2%) were identified. Human labour, pesticide, seeds and indirect energy for machinery use had marginal importance, contributing only 0.2%, 0.6%, 6.8% and 6.9%, respectively to the total energy consumption. Focusing on the operational energy consumption for the lowland rice production, the main energy use was in field cultivation activities (23 10.24 MJIha; 64.2%, planting included) and harvesting ( I 171.44 ~ J h a - '3: 2.6%). while spreading of fertilizer and pesticide had only little importance within total mechanization. Indirect energy use for mechanization took about 848.95 ha-' or 23.6% from total energy use for mechanization of 3595.87 h ha-'. Compared to total energy demand of 12225.97 h ha-I. indirect energy use for mechanization was even less important (6.9%). Average grain yield was 6470.8 kg ha-', representing energy output of 108321.75 mJha - 'that is, 96095.78 MJ net energy gain or 8.86 MJ output per MJ input. Energy input per kilogram grain yield was 1.89 M J ~ ~ -T' .h e simulation results obtained from the developed computer program regarding direct and indirect operational energy consumption in the lowland rice production were consistent with those obtained from the field study. The results of the study could serve as a guide to lowland rice farmers in other geographical locations in achieving their production goals. Improvements could be made through the application of the simulation model by figuring out the energy input requirements for all possible combinations of field operations for lowland rice production. It is suggested, as a consequence of this research, that paddy farmers in the Tanjong Karang Rice Irrigation Scheme of Malaysia and other schemes with similar operational conditions adopt the use of Gear 1 High and rotary tilling speed of 175 rpm for tillage operations. The application of this practice should reduce the excessive demand on fossil fuel energy which currently is very expensive and whose continuous availability is unpredictable. This will assist in the on-going campaign to minimize the flux of hard currency out of most developing and transition countries in the form of energy bills. The results and recommendations here are based on the available data on the current practices involved in the lowland rice production system of Malaysia and hence are useful for the current lowland rice crop planning and farm management practices.